PENGEMBANGAN MEDIA LEMBAR BALIK GIZI SEIMBANG PADA BALITA UNTUK MENINGKATKAN PENGETAHUAN KADER POSYANDU (Jurnal Kesehatan Siliwangi, 2021)
Nutritional status is one of the important factors in achieving optimal health status. The Nutritional Status Below the Red Line (BGM) in Bojongsoang District is 89 children under five (Bandung District Health Profile, 2018). Buahbatu Village is one of the villages in Bojongsoang District, Bandung Regency. Posyandu cadres are the main driver of all activities carried out at posyandu. The results of pre-research interviews with posyandu cadres in Buahbatu Village, stated that the knowledge of posyandu cadres regarding balanced nutrition in toddlers was not optimal. Increased knowledge can be done with health education using health promotion media. One of the media that is often used in health education is flipchart. The purpose of this study was to produce a balanced nutrition sheet media for toddlers and their impact on increasing the knowledge of posyandu cadres in Buahbatu Village, Bandung Regency. This study uses the media development method with the ADDIE approach, to measure the effect on changes in knowledge of Posyandu cadres, the One Group Pretest Posttest approach without control is used. The sampling technique used is total sampling. The data used in this study are primary data through the assessment of health promotion media by media experts and material experts, as well as pretest and posttest questionnaires to measure the increase in knowledge of posyandu cadres about balanced nutrition in toddlers. Data analysis used univariate and bivariate with paired sample t-test at 0,05. The results showed an increase in knowledge from 50.20 to 67.20 and the results of data analysis obtained a p value of 0,000 < 0,05. Shows that the use of balanced nutrition sheet media for toddlers has a significant effect on increasing knowledge of posyandu cadres in Buahbatu Village, Bandung Regency.